(untitled) (Journal of Bangladesh Academy of Sciences, 2020)
This paper deals with a variant of the classical Tower of Hanoi problem with n ( ≥ 1) discs, of which r discs are evildoers, each of which can be placed directly on top of a smaller disc any number of times. Denoting by E(n, r) the minimum number of moves required to solve the new variant, is given a scheme find the optimality equation satisfied by E(n, r). An explicit form of E(n, r) is then obtained. Journal of Bangladesh Academy of Sciences, Vol. 43, No. 2, 205-209, 2019